Larger drupe size and earlier geminants for better seedling attributes of teak (Tectona grandis Linn. f.) - C.M. Jijeesh; K. Sudhakar (Annals of Forest Research, 2013)
Massive plantation establishment programme in the tropics hasled to an ever-increasing demand for good quality planting stock of teak (Tectona grandis L. f.). Although drupe size in teak is positively correlated with seedling growth much less is known about the combined effect of drupe size and time of emergence on the performance of the seedlings.The drupes were divided in 3 diameter categories (i.e. 9-12, 12-15and 15-18 mm) and the number of germinants were weekly counted forfour weeks. The resulted seedlings were planted in poly bags containingrooting medium of soil and sand (1:1 ratio). Results of the study indicated that the seedling emergence was largest during second week irrespective of drupe size. Seedlings from 15-18 mm diameter class drupes recorded the highest seedling attributes followed by 12-15 mm and 9-12 mm classes.However, net assimilation rate and relative growth rate were highest in the seedlings obtained from 9-12 mm class drupes. With a few exceptions, first week emergents recorded the highest seedling attributes followed by second, third and fourth week germinants. Cluster analysis of the seedling attributes identified the seedlings belonging to 15-18 mm drupe size and emerging during first week as superior. But, considering the largest number of drupes in 12-15 mm size class, peak germination during second week after sowing, price of planting stock and cost of nursery operation per unit of planting, second week germinants of 12–15 mm size drupes can also be recommended for raising seedlings in plantation programmes of teak.